Characterization of original research presented at the COVID-19 First National Scientific Conference , CovidCien2021 - Luis Enrique Jiménez Franco; Claudia Díaz de la Rosa; Jayce Díaz Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: original investigations represent the fulfillment of a research process; it test all the research team's abilities, from detecting the problem and conducting the study to interpreting the results and proposing solutions to the problem. Objective: to characterize the original research presented at the COVID-19 First National Scientific Conference, CovidCien2021. Methods: an observational, descriptive, cross-sectional study was carried out. 57 papers presented at the event were included. Variables: number of original researches presented, student investigations or professional investigations, type of study, type of research, most common methodological errors, number of authors. Descriptive statistics were used for processing and analysis of the results. Results: 57 free topics were presented (32.6%). Research belonging to students stood out (32; 56.1%). Descriptive observational studies (50; 87.7%) and quantitative studies (50; 87.7%) stood out. Papers with four and five authors prevailed (14; 24.6%). Difficulties such as the absence of the research objective and errors in the methodology that make its reproduction impossible were observed. Conclusions: descriptive observational researches, mostly quantitative, provide general and particular elements of a problem. There is a need to educate future generations in good methodological practices, in order to achieve science of quality and excellence.